Managing innovation - Tidd, Joseph; Bessant, J. R. (John Wiley & Sons, 2018)
Managing Innovation provides readers with the knowledge to understand, and the skills to manage, innovation at the operational and strategic levels. Specifically, it integrates the management of market, organizational and technological change to improve the competitiveness of firms and effectiveness of other organizations.